2011
DOI: 10.1029/2010jd014598
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spectral dispersion on clouds and precipitation in mesoscale convective systems

Abstract: [1] The effects of spectral dispersion on clouds and precipitation in mesoscale convective systems have been studied by conducting 10 numerical simulations with different values of spectral dispersion (" = 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and 1.0) in the clean, semipolluted, and polluted backgrounds. The simulation results show that spectral dispersion affects cloud microphysical properties markedly in each aerosol regime. With an increase in spectral dispersion, both the raindrop concentration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
(51 reference statements)
4
12
0
Order By: Relevance
“…It is suggested that, compared with the autoconversion rate, there is relatively more efficient accretion growth with higher cloud water contents in the polluted backgrounds (see Table 3 for PRA), which eventually results in larger radius of rain drops. Aerosols can increase the rain drop size, which is in general good agreement with previous studies (Cheng et al, 2007;Altaratz et al, 2008;Berg et al, 2008;Li et al, 2008;Li et al, 2009;Lim and Hong, 2010;Storer et al, 2010;Lim et al, 2011;Xie and Liu, 2011).…”
Section: Liquid Cloud Microphysical Propertiessupporting
confidence: 88%
See 3 more Smart Citations
“…It is suggested that, compared with the autoconversion rate, there is relatively more efficient accretion growth with higher cloud water contents in the polluted backgrounds (see Table 3 for PRA), which eventually results in larger radius of rain drops. Aerosols can increase the rain drop size, which is in general good agreement with previous studies (Cheng et al, 2007;Altaratz et al, 2008;Berg et al, 2008;Li et al, 2008;Li et al, 2009;Lim and Hong, 2010;Storer et al, 2010;Lim et al, 2011;Xie and Liu, 2011).…”
Section: Liquid Cloud Microphysical Propertiessupporting
confidence: 88%
“…x c can be written as a formula x c ¼ 9:7 Â 10 À17 N 3=2 c L À2 c . In a previous study (Xie and Liu, 2011), a similar autoconversion parameterisation was adopted where the cloud droplet spectral dispersion is a fixed constant (o 00.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0). However, in this article, o is parameterised as the function of the cloud droplet number concentration N c , described by the functions eq.…”
Section: Parameterisations Of Autoconversion Process and Wrf Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in the magnitude of these impacts were also evident for the baseline model configuration with small perturbations to the vertical shear of the environmental u-component wind. These changes were of similar magnitude to changes in aerosol effects on deep convective storms with altered microphysics process formulations reported in previous studies (Ekman et al, 2011;Xie and Liu, 2011). Thus, the rapid growth of small perturbations and limits on the predictability of convective systems can potentially obscure sensitivity of aerosol effects to different model configurations and parameterizations, especially for studies of individual storms.…”
Section: Discussionsupporting
confidence: 51%